2001
DOI: 10.1037/1076-898x.7.4.331
|View full text |Cite
|
Sign up to set email alerts
|

Judging the accuracy of children's recall: A statement-level analysis.

Abstract: Three experiments were conducted to examine fact finders' judgments of children's answers to cued recall questions about a recent dental visit. Participants performed better than chance at judging the correctness of the children's answers in all 3 experiments, and judgment accuracy was consistently better when the children's answers were correct. Judgment performance did not decline when confidence information was removed, and when all confidence information was removed, the best performance was obtained by pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
(61 reference statements)
4
20
0
Order By: Relevance
“…The findings from this study support several previous studies [2,8] in showing that while different professional groups do not perform at greater than chance levels in correctly judging the accuracy of children's testimony those who have children of their own do show a significant advantage in performance. Parents performed at significantly greater than chance levels in correctly classifying all of the enrolled children.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The findings from this study support several previous studies [2,8] in showing that while different professional groups do not perform at greater than chance levels in correctly judging the accuracy of children's testimony those who have children of their own do show a significant advantage in performance. Parents performed at significantly greater than chance levels in correctly classifying all of the enrolled children.…”
Section: Discussionsupporting
confidence: 81%
“…Similar performance rates are observed in adult detection of children's deception [2,7] suggested from their study that parents did better than non-parents in correctly identifying when children were lying or being truthful in a series of video presentations. [8] carried out three experimental studies on participant's performance in judging the correctness of children's recall of a recent visit to the dentist. They found that participants were better at judging when children were correctly reporting the event and did less well when the children were incorrectly reporting details.…”
Section: Introductionmentioning
confidence: 99%
“…In these kinds of studies adults typically have considerable difficulty evaluating the truthfulness of accounts from children (Ball & O'Callaghan, 2001;Block et al, 2012;Laimon & Poole, 2008;Leippe, Manion, & Romanczyk, 1992;Qin, Ogle, & Goodman, 2008) or from adults reporting childhood events (Ost, Vrij, Costall, & Bull, 2002;Schooler, Gerhard, & Loftus, 1986). Even the ability of experts to discern true from false reports is uniformly poor; in many instances professionals are no better than chance and some are reliably worse (Bond & DePaulo, 2006;Ekman, O'Sullivan, & Frank, 1999;Erdmann et al, 2004;Kassin, Meissner, & Norwick, 2005;Leichtman & Ceci, 1995;Vrij & Mann, 2001).…”
Section: Expert Opinion About Children's Testimonymentioning
confidence: 97%
“…For example, Ball and O'Callaghan (2001) examined the question of whether student participants could discriminate accurate statements from inaccurate children's answers to cued recall questions about a recent dental visit. They found that, at the statement or question level, the average success rates for these judgements were better than those predicted by simply guessing correctly.…”
Section: Introductionmentioning
confidence: 99%